Abutment pressure distribution for longwall face mining through abandoned roadways - Li, Yang; Lei, Mingxing; Wang, Haosen; Li, Cheng; Li, Weiwei; Tao, Yang; Wang, Jingyi (International journal of mining science and technology, 2019)
Abutment pressure distribution is different when a longwall panel is passing through the abandoned gate roads in a damaged coal seam. According to the geological condition of panel E13103 in Cuijiazhai Coal Mine in China, theoretical analysis and finite element numerical simulation were used to determine the front pressure distribution characteristics when the longwall face is 70, 50, 30, 20, 10, and 5 m from the abandoned roadways. The research results show that the influence range of abutment pressure is 40 to 45 m outby the face, and the peak value of front abutment pressure is related to the distance between the face and abandoned roadways. When the distance between the longwall face and abandoned roadways is reduced from 50 to 10 m, the front abutment pressure peak value kept increasing. When the distance is 10 m, it has reached the maximum. The peak value is located in 5 to 6 m outby the faceline. When the distance between the longwall face and abandoned roadways is reduced from10 to5 m, the front abutment pressure sharply decreases, the intact coal yields and is even in plastic state. The peak value transfers to the other side of the abandoned roadways. The research results provide a theoretical basis for determining the advance support distance of two roadways in the panel and the reinforcement for face stability when the longwall face is passing through the abandoned roadways.